Non invasive mechanic ventilation in patients with acute chronic obstructive lung disease in intensive cares: ten years of experience - Zadis Navarro Rodríguez; Julio César González Aguilera; Lázaro Ibrahim Romero García; José Manuel Torres Maceo; Liudis Bigñot Favier (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: The non invasive ventilation is an effective treatment in patients with acute lung disease. Objective: To describe the demographic, clinical, ventilatory and hemogasometric characteristics in patients treated with non invasive ventilation. Methods: An observational, descriptive, longitudinal and prospective study of 234 patients with chronic obstructive lung disease, non-invasive ventilated in the Intensive Cares Unit of Saturnino Lora Teaching Clinical-Surgical Provincial Hospital in Santiago de Cuba, was carried out, from January, 2011 to September, 2021. Results: In the series there was a prevalence of male sex, non hospital acquired pneumonia and chronic heart failure; while the mean age was 71 years and non invasive ventilation failed in 53.8 % of those affected. Also, the respiratory rate decreased from 34.3 to 23.5 breaths per minute in the second hour and an increase in pH was also observed, as well as in the relationship arterial pressure of O2/inspired fraction of O2 and oxygen saturation to the pulsioximetry/inspiratory fraction of O2. The arterial pressure of CO2 had average values of 61.8 mmHg to the beginning and of 60.7 mmHg in the second hour. Conclusions: The basal values of clinical, hemogasometric and ventilatory variables improved after treatment with non invasive ventilation. Among the parameters associated with the treatment failure there were heart frequency, respiratory frequency, arterial pressure of CO2, coma Glasgow scale, pH and leaks; equally, the long stay, the ventilation for more than 48 hours and mortality were related to this failure.